Regulation of melanocyte stem cells in the pigmentation of skin and its appendages: Biological patterning and therapeutic potentials. Issue 4 (15th January 2019) - Qiu, Weiming; Chuong, Cheng‐Ming; Lei, Mingxing
Abstract: Skin evolves essential appendages and indispensable types of cells that synergistically insulate the body from environmental insults. Residing in the specific regions in the skin such as epidermis, dermis and hair follicle, melanocytes perform an array of vital functions including defending the ultraviolet radiation and diversifying animal appearance. As one of the adult stem cells, melanocyte stem cells in the hair follicle bulge niche can proliferate, differentiate and keep quiescence to control and coordinate tissue homeostasis, repair and regeneration. In synchrony with hair follicle stem cells, melanocyte stem cells in the hair follicles undergo cyclic activation, degeneration and resting phases, to pigment the hairs and to preserve the stem cells. Disorder of melanocytes results in severe skin problems such as canities, vitiligo and even melanoma. Here, we compare and summarize recent discoveries about melanocyte in the skin, particularly in the hair follicle. A better understanding of the physiological and pathological regulation of melanocyte and melanocyte stem cell behaviours will help to guide the clinical applications in regenerative medicine.